Lightweight multidimensional feature enhancement algorithm LPS-YOLO for UAV remote sensing target detection - Yong Lu; Minghao Sun (Scientific Reports)
Abstract Detecting small targets in UAV remote sensing images is challenging for traditional lightweight methods due to difficulty in feature extraction and high background interference. We propose LPS-YOLO, which improves small target feature extraction while reducing computational complexity by replacing the Conv backbone with SPDConv to retain fine-grained features. LPS-YOLO introduces the SKAPP module for better feature fusion and incorporates the E-BiFPN and OFTP structures to efficiently preserve and transfer backbone information. Evaluation of the VisDrone2019 dataset shows a 17.3% increase in mean Average Precision (mAP) and a 42.5% reduction in parameters compared to the baseline. Additional experiments on the DOTAv2 dataset demonstrate the model’s robustness, with a 14.5% improvement in F1 score and a 14.9% increase in mAP over YOLOv8-n. LPS-YOLO offers an effective solution for multi-target detection in UAVs.